Working the ‘in-between-spaces’ for transformation within the academy - Shirley Walters (South African Journal of Education, 2018)
This paper considers the importance of ‘in-between spaces’ within the academy for challenging dominant institutional culture and hegemonic power relations towards a ‘de-colonised’ university. It questions ‘mainstreaming’ of transformational initiatives, as this can bring about regulation, rather than the turbulence that is often what is needed for substantive change to occur. I draw on a case study of the work of the Division for Lifelong Learning (DLL) at University of the Western Cape and in particular two examples of its marginal activities which were hosted regularly over a 10 year period. These are: the Vice-Chancellor’s Annual Julius Nyerere Lecture on Lifelong Learning and the cross-campus Annual Women’s Breakfast. I use documentary evidence and insider knowledge to reflect critically on the relevance of the spaces that were created for enacting such alternative institutional practices. I employ ‘knowledge democracy’ as a lens to bring the margins to the centre of the analysis. The argument is made that the work in the ‘in-between-spaces’ is a critical part of ‘decolonising education’ through disruptive, political, pedagogical, and organisational transformation.